Deep eutectic-based magnetic molecularly imprinted polymer as well as preparation method and application thereof
Through the preparation of deep eutectic-based magnetic molecular imprinting polymer, the rapid and accurate problems of doxycycline adsorption and separation are solved by using Fe3O4@SiO2-CH=CH2 carrier and surface imprinting technology, and high selectivity and low The cost of adsorption effect is suitable for doxycycline detection in complex substrates.
Patent Information
- Application Number
- CN202411500360.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to quickly and accurately adsorb and separation of doxycycline, especially in detection and monitoring in complex substrates.
The preparation method of deep eutectic-based magnetic molecular imprinted polymer was prepared by Fe3O4@SiO2-CH=CH2 as a carrier, combined with coprecipitation method, sol-gel method and surface blotting method, and prepared with magnetic and high selective adsorption ability. Deep eutectic-based magnetic molecular imprinted polymers for adsorption and separation of doxycycline.
It realizes rapid and accurate adsorption and separation of doxycycline, with high selectivity and stability, simplifies the processing process, reduces costs, and can quickly achieve solid-liquid separation under the applied magnetic field, shortening the processing time.
Smart Images

Figure CN119219869A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of imprinted polymer preparation, and in particular to a deep eutectic-based magnetic molecular imprinted polymer and a preparation method and application thereof. Background Art
[0002] Molecular imprinting technology (MIT) is a molecular recognition technology based on the principle of antigen-antibody interaction. Its application is an interesting way to obtain highly selective analytical systems. Usually, functional monomers are self-assembled around the template, and a polymer that completely matches the template in terms of spatial structure and binding sites is synthesized in the presence of a wide range of cross-linking agents to facilitate analysis and determination in different matrices. The prepared molecularly imprinted polymers (MIPs) have three major characteristics: structural predictability, recognition specificity, and universal application, which are the main advantages of imprinted materials in the pretreatment of complex matrices and low-content analyte samples. According to research needs and the advantages of simplicity and low cost of preparation, the preparation of different forms of imprinted materials suitable for specific extraction techniques has become a diversified research goal.
[0003] Doxycycline (DOX) is usually a yellow crystalline powder. Due to its high oral absorption rate and good antibacterial effect, it has become the most sensitive and safe broad-spectrum antibacterial, anti-mycoplasma and anti-chlamydia drug in clinical veterinary medicine. In addition, in life, doxycycline is widely found in livestock and poultry products, such as poultry and seafood products. According to regulations issued by the European Union, the maximum residue limit of DOX in poultry muscle is 100μg / kg. China and Japan stipulate that the maximum residue limit of doxycycline in fish meat is 100μg / kg and 50μg / kg respectively. It is urgent to conduct rapid and accurate monitoring of doxycycline in livestock and poultry food. Summary of the invention
[0004] The object of the present invention is to provide a deep eutectic-based magnetic molecular imprinted polymer and a preparation method and application thereof, so as to solve the technical problem of rapid and accurate adsorption and separation of doxycycline.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a deep eutectic-based magnetic molecular imprinted polymer, comprising the following steps:
[0007] (1) Fe 3 O 4 Dispersed in ethanol aqueous solution, then added with ammonia water and ethyl orthosilicate for reaction, the reaction product was collected and dried to obtain Fe 3 O 4 @SiO 2 ;
[0008] (2) Mix 3-methacryloxypropyltrimethoxysilane in anhydrous ethanol and then add Fe 3 O 4 @SiO 2 The reaction was carried out, and the reaction product was collected and dried to obtain Fe 3 O 4 @SiO 2 -CH=CH 2 ;
[0009] (3) Prepolymerization of doxycycline and DES functional monomers in methanol, followed by addition of Fe 3 O 4 @SiO 2 -CH=CH 2 A secondary prepolymerization reaction is carried out, and then a crosslinking agent and an initiator are added to carry out a polymerization reaction. The reaction product is collected and dried to obtain a deep eutectic-based magnetic molecular imprinted polymer.
[0010] Furthermore, the Fe 3 O 4 , ammonia water and tetraethyl orthosilicate in a dosage ratio of 0.9-1.1 g: 3-5 mL: 2-3 mL; the Fe 3 O 4 The mass volume ratio of the ethanol aqueous solution is 0.9-1.1 g: 200-300 mL.
[0011] Furthermore, in step (1), the reaction temperature is 20 to 40° C., and the reaction time is 7 to 9 hours;
[0012] The ethanol aqueous solution is obtained by mixing ethanol and water in a volume ratio of 3 to 5:1.
[0013] Furthermore, the 3-methacryloxypropyltrimethoxysilane, anhydrous ethanol and Fe 3 O 4 @SiO 2 The dosage ratio is 6-10mL:150-170mL:0.3-0.5g.
[0014] Furthermore, in the step (2), the reaction is carried out under nitrogen protection, the reaction temperature is 60-70° C., and the reaction time is 11-13 h.
[0015] Further, the usage ratio of doxycycline, DES functional monomer and methanol is 0.190-0.223 g: 0.3-0.37 mL: 40-60 mL;
[0016] The doxycycline and Fe 3 O 4 @SiO 2-CH=CH 2 The mass ratio is 0.190~0.223:0.15~0.25.
[0017] Furthermore, the prepolymerization reaction temperature is 20 to 30° C. and the time is 1 to 4 hours;
[0018] The secondary prepolymerization reaction time is 8 to 10 hours.
[0019] Furthermore, the dosage ratio of the doxycycline, the crosslinking agent and the initiator is 0.190-0.223 g: 3-4 mL: 0.04-0.06 g; the polymerization reaction is carried out under nitrogen protection, the polymerization reaction temperature is 55-65° C., and the polymerization reaction time is 10-14 h;
[0020] The crosslinking agent comprises ethylene glycol dimethacrylate, and the initiator comprises azobisisobutyronitrile.
[0021] The invention provides a deep eutectic-based magnetic molecular imprinted polymer.
[0022] The present invention also provides a use of a deep eutectic-based magnetic molecular imprinted polymer as a doxycycline adsorbent.
[0023] Beneficial effects of the present invention:
[0024] The present invention integrates the coprecipitation method, the sol-gel method and the surface imprinting method to first prepare a clear, transparent and stable DES monomer, and then prepare a black nano-magnetic Fe 3 O 4 , Fe prepared by silanization and vinylization 3 O 4 @SiO 2 -CH=CH 2 The texture is uniform and fine, the dispersibility is good, the operation is simple, and the reaction solvent and time are saved. The deep eutectic-based magnetic molecular imprinting is obtained by reaction during mechanical stirring. The particle size is uniform and the diameter is small, which can achieve the specific adsorption of doxycycline. The polymer preparation cost is low. Because of its magnetic properties, it can quickly achieve solid-liquid separation under an external magnetic field, shortening the processing time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Scanning electron microscopy images of deep eutectic-based magnetic molecular imprinted polymers ((a) DES-MMIP; (b) DES-MNIP);
[0026] Figure 2 Infrared spectra of different products in the preparation process (a) Fe 3 O 4 ; (b) Fe 3 O 4@SiO 2 ; (c) DES-MMIP);
[0027] Figure 3 The X-ray diffraction patterns of different products in the preparation process (a) Fe 3 O 4 ; (b) Fe 3 O 4 @SiO 2 ; (c) DES-MMIP);
[0028] Figure 4 Thermogravimetric analysis of different products in the preparation process (a) Fe 3 O 4 ; (b) Fe 3 O 4 @SiO 2 ; (c) DES-MMIP);
[0029] Figure 5 The hysteresis loops of different products in the preparation process (a)Fe 3 O 4 ; (b)
[0030] Fe 3 O 4 @SiO 2 -CH=CH 2 ; (c) DES-MMIP);
[0031] Figure 6 It is the dynamic adsorption curve of deep eutectic-based magnetic molecular imprinted polymer;
[0032] Figure 7 It is the static adsorption curve of deep eutectic-based magnetic molecular imprinted polymer;
[0033] Figure 8 This is the selective adsorption curve of deep eutectic-based magnetic molecular imprinted polymer. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a deep eutectic-based magnetic molecular imprinted polymer, comprising the following steps:
[0035] (1) Fe 3 O 4 Dispersed in ethanol aqueous solution, then added with ammonia water and ethyl orthosilicate for reaction, the reaction product was collected and dried to obtain Fe 3 O 4 @SiO 2 ;
[0036] (2) Mix 3-methacryloxypropyltrimethoxysilane in anhydrous ethanol and then add Fe3 O 4 @SiO 2 The reaction was carried out, and the reaction product was collected and dried to obtain Fe 3 O 4 @SiO 2 -CH=CH 2 ;
[0037] (3) Prepolymerization of doxycycline and DES functional monomers in methanol, followed by addition of Fe 3 O 4 @SiO 2 -CH=CH 2 A secondary prepolymerization reaction is carried out, and then a crosslinking agent and an initiator are added to carry out a polymerization reaction. The reaction product is collected and dried to obtain a deep eutectic-based magnetic molecular imprinted polymer.
[0038] In the present invention, the Fe 3 O 4 The preparation method comprises the following steps:
[0039] Weigh 5.2-5.4 g FeCl 3 6H 2 O and 1.8-2.0 g FeCl 2 ·4H 2 O, add 70-90 mL of deionized water, add 11-13 mL of concentrated ammonia, N 2 Under protection, the mixture was heated and stirred vigorously for 30 min. After the reaction was completed, the reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and vacuum dried to obtain Fe 3 O 4 .
[0040] Preferably, weigh 5.3 g FeCl 3 6H 2 O and 1.9 g FeCl 2 ·4H 2 O, add 80mL of deionized water, add 12mL of concentrated ammonia, N 2 Under protection, the mixture was heated and stirred vigorously for 30 min. After the reaction was completed, the reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and vacuum dried to obtain Fe 3 O 4 .
[0041] In the present invention, the Fe 3 O 4 In the preparation method, the heating temperature is 75 to 85°C, preferably 78 to 82°C, and more preferably 80°C.
[0042] In the present invention, the Fe 3 O 4, ammonia water and tetraethyl orthosilicate in an amount ratio of 0.9-1.1 g: 3-5 mL: 2-3 mL, preferably 1.0 g: 4 mL: 2.5 mL; the Fe 3 O 4 The mass volume ratio of the ethanol aqueous solution is 0.9-1.1 g:200-300 mL, preferably 1.0 g:250 mL.
[0043] In the present invention, in the step (1), the reaction temperature is 20 to 40° C., preferably 25 to 35° C.; the reaction time is 7 to 9 hours, preferably 8 hours.
[0044] In the present invention, the ethanol aqueous solution is obtained by mixing ethanol and water in a volume ratio of 3 to 5:1, preferably 4:1.
[0045] In the present invention, the 3-methacryloxypropyltrimethoxysilane, anhydrous ethanol and Fe 3 O 4 @SiO 2 The dosage ratio is 6-10 mL: 150-170 mL: 0.3-0.5 g, preferably 7-9 mL: 155-165 mL: 0.35-0.45 g, and more preferably 8 mL: 160 mL: 0.4 g.
[0046] In the present invention, in the step (2), the reaction is carried out under nitrogen protection, the reaction temperature is 60-70°C, preferably 62-68°C, and more preferably 65°C; the reaction time is 11-13h, preferably 12h.
[0047] In the present invention, the usage ratio of doxycycline, DES functional monomer and methanol is 0.190-0.223 g: 0.3-0.37 mL: 40-60 mL, preferably 0.220 g: 0.35 mL: 50 mL.
[0048] In the present invention, the preparation method of the DES functional monomer comprises the following steps:
[0049] Take 13.96 g of hydrogen bond acceptor choline chloride and 172 uL of hydrogen bond donor methacrylic acid, and react at 80° C. with constant stirring until clear and transparent, thereby forming a stable DES monomer.
[0050] In the present invention, the doxycycline and Fe 3 O 4 @SiO 2 -CH=CH 2 The mass ratio is 0.190-0.223:0.15-0.25, preferably 0.220:0.20.
[0051] In the present invention, the prepolymerization reaction temperature is 20-30°C, preferably 25°C; the time is 1-4h, preferably 3h.
[0052] In the present invention, the secondary prepolymerization reaction time is 8 to 10 hours, preferably 9 hours.
[0053] In the present invention, the dosage ratio of doxycycline, cross-linking agent and initiator is 0.190-0.223g:3-4mL:0.04-0.06g, preferably 0.220g:3.5mL:0.05g; the polymerization reaction is carried out under nitrogen protection, the polymerization reaction temperature is 55-65°C, preferably 58-62°C, and more preferably 60°C; the polymerization reaction time is 10-14h, preferably 12h.
[0054] In the present invention, the crosslinking agent is preferably ethylene glycol dimethacrylate, and the initiator is preferably azobisisobutyronitrile.
[0055] The invention provides a deep eutectic-based magnetic molecular imprinted polymer.
[0056] The present invention also provides a use of a deep eutectic-based magnetic molecular imprinted polymer as a doxycycline adsorbent.
[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0058] Example 1
[0059] A method for preparing a deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) comprises the following steps:
[0060] (1) Preparation of DES monomer: (1) Take 13.96 g of choline chloride and 172 uL of methacrylic acid, and react at 80° C. with constant stirring until clear and transparent to form a stable DES monomer;
[0061] (2) Preparation of Fe by coprecipitation 3 O 4 :Weigh FeCl 3 6H 2 O (5.2 g) and FeCl 2 ·4H 2 O (1.8 g), add 70 mL of deionized water, 11 mL of concentrated ammonia, N 2 Under protection, the reaction was stirred vigorously at 75°C for 30 min. After the reaction was completed, the reaction product was collected with a magnetic core, washed with deionized water until neutral, and vacuum dried to obtain Fe 3 O 4 Nanoparticles;
[0062] (3) Preparation of silanized Fe by sol-gel method 3 O 4 :Weigh Fe 3 O 4 (0.9 g) was completely dispersed in 200 mL of ethanol-water (4:1, V / V) solution, concentrated ammonia (3 mL) and TEOS (2 mL) were added, and stirred at room temperature for 7 h. After the reaction was completed, the reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and vacuum dried to obtain silanized Fe 3 O 4 Nanoparticles (Fe 3 O 4 @SiO 2 );
[0063] (4) Vinyl Fe 3 O 4 @SiO 2 Preparation: 3-methacryloxypropyltrimethoxysilane (6 mL) was dissolved in 170 mL of anhydrous ethanol, and then Fe 3 O 4 @SiO 2 (0.35 g), N 2 The reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and dried under vacuum at 50°C to obtain solid particles, namely Fe 3 O 4 @SiO 2 -CH=CH 2 ;
[0064] (5) Preparation of deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) by surface imprinting method: 0.190 g of doxycycline, 0.30 mL of functional monomer (DES) and 40 mL of methanol were placed in a 250 mL three-necked flask and prepolymerized at 25 °C for 1 h. Then, Fe 3 O 4 @SiO 2 -CH=CH 2 (0.20 g), continued prepolymerization for 11 h, then added 3.5 mL of crosslinker ethylene glycol dimethacrylate (EGDMA) and initiator azobisisobutyronitrile (AIBN, 0.04 g), and ultrasonically mixed for 10 min. 2 Under protection, the reaction was stirred at 65 °C for 11 h. After the reaction was completed, the reaction product was collected with a magnetic core, and the template was eluted with methanol:acetic acid (9:1, V / V) until doxycycline could not be detected in the eluent. The acetic acid was then removed by elution with ethanol and deionized water, and the product was dried in vacuo at 50 °C to obtain a deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP).
[0065] Example 2
[0066] A method for preparing a deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) comprises the following steps:
[0067] (1) Preparation of DES monomer: (1) Take 13.96 g of choline chloride and 172 uL of methacrylic acid, and react at 80° C. with constant stirring until clear and transparent to form a stable DES monomer;
[0068] (2) Preparation of Fe by coprecipitation 3 O 4 :Weigh FeCl 3 6H 2 O (5.3 g) and FeCl 2 ·4H 2 O (1.95 g), add 90 mL of deionized water, 13 mL of concentrated ammonia, N 2 Under protection, the reaction was stirred vigorously at 85°C for 30 min. After the reaction was completed, the reaction product was collected with a magnetic core, washed with deionized water until neutral, and dried in vacuum to obtain Fe 3 O 4 Nanoparticles;
[0069] (3) Preparation of silanized Fe by sol-gel method 3 O 4 :Weigh Fe 3 O 4 (1.1 g) was completely dispersed in 300 mL of ethanol-water (4:1, V / V) solution, concentrated ammonia (5 mL) and TEOS (2.5 mL) were added, and stirred at room temperature for 9 h. After the reaction was completed, the reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and vacuum dried to obtain silanized Fe 3 O 4 Nanoparticles (Fe 3 O 4 @SiO 2 );
[0070] (4) Vinyl Fe 3 O 4 @SiO 2 Preparation: 3-methacryloxypropyltrimethoxysilane (10 mL) was dissolved in 150 mL of anhydrous ethanol, and then Fe 3 O 4 @SiO 2 (0.45g), N 2 The reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and dried under vacuum at 50°C to obtain solid particles, namely Fe 3 O 4 @SiO 2-CH=CH 2 ;
[0071] (5) Preparation of deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) by surface imprinting method: 0.216 g of doxycycline, 0.32 mL of functional monomer (DES) and 60 mL of methanol were placed in a 250 mL three-necked flask and prepolymerized at 25 °C for 4 h. Then, Fe 3 O 4 @SiO 2 -CH=CH 2 (0.20 g), continue prepolymerization for 8 h, then add 3.7 mL of crosslinker ethylene glycol dimethacrylate (EGDMA) and initiator azobisisobutyronitrile (AIBN, 0.06 g), mix ultrasonically for 10 min, and 2 Under protection, the reaction was stirred at 55 °C for 12 h. After the reaction was completed, the reaction product was collected with a magnetic core, and the template was eluted with methanol:acetic acid (9:1, V / V) until doxycycline could not be detected in the eluent. The acetic acid was then removed by elution with ethanol and deionized water, and the product was dried in vacuo at 50 °C to obtain a deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP).
[0072] Example 3
[0073] A method for preparing a deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) comprises the following steps:
[0074] (1) Preparation of DES monomer: (1) Take 13.96 g of choline chloride and 172 uL of methacrylic acid, and react at 80° C. with constant stirring until clear and transparent to form a stable DES monomer;
[0075] (2) Preparation of Fe by coprecipitation 3 O 4 :Weigh FeCl 3 6H 2 O (5.4 g) and FeCl 2 ·4H 2 O (2.0 g), add 80 mL of deionized water, 12 mL of concentrated ammonia, N 2 Under protection, the reaction was stirred vigorously at 80°C for 30 min. After the reaction was completed, the reaction product was collected with a magnetic core, washed with deionized water until neutral, and vacuum dried to obtain Fe 3 O 4 Nanoparticles;
[0076] (3) Preparation of silanized Fe by sol-gel method 3 O 4 :Weigh Fe 3 O 4(1.0 g) was completely dispersed in 250 mL of ethanol-water (4:1, V / V) solution, concentrated ammonia (4 mL) and TEOS (3 mL) were added, and stirred at room temperature for 8 h. After the reaction was completed, the reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and vacuum dried to obtain silanized Fe 3 O 4 Nanoparticles (Fe 3 O 4 @SiO 2 );
[0077] (4) Vinyl Fe 3 O 4 @SiO 2 Preparation: 3-methacryloxypropyltrimethoxysilane (8 mL) was dissolved in 160 mL of anhydrous ethanol, and then Fe 3 O 4 @SiO 2 (0.4g), N 2 The reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and dried under vacuum at 50°C to obtain solid particles, namely Fe 3 O 4 @SiO 2 -CH=CH 2 ;
[0078] (5) Preparation of deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) by surface imprinting method: 0.222 g of doxycycline, 0.35 mL of functional monomer (DES) and 50 mL of methanol were placed in a 250 mL three-necked flask and prepolymerized at 25 °C for 3 h. Then, Fe 3 O 4 @SiO 2 -CH=CH 2 (0.20 g), continue prepolymerization for 9 h, then add 4 mL of crosslinking agent ethylene glycol dimethacrylate (EGDMA) and initiator azobisisobutyronitrile (AIBN, 0.05 g), mix ultrasonically for 10 min, and then add N 2 Under protection, the reaction was stirred at 60 °C for 12 h. After the reaction, the reaction product was collected with a magnetic core, and the template was eluted with methanol:acetic acid (9:1, V / V) until doxycycline could not be detected in the eluent. The acetic acid was then removed by elution with ethanol and deionized water, and the product was dried in vacuo at 50 °C to obtain a deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP).
[0079] Example 4
[0080] A method for preparing a deep eutectic-based magnetic molecular imprinted polymer (DES-MNIP) comprises the following steps:
[0081] (1) Preparation of DES monomer: (1) Take 13.96 g of choline chloride and 172 uL of methacrylic acid, and react at 80° C. with constant stirring until clear and transparent to form a stable DES monomer;
[0082] (2) Preparation of Fe by coprecipitation 3 O 4 :Weigh FeCl 3 6H 2 O (5.4 g) and FeCl 2 ·4H 2 O (2.0 g), add 80 mL of deionized water, 12 mL of concentrated ammonia, N 2 Under protection, the reaction was stirred vigorously at 80°C for 30 min. After the reaction was completed, the reaction product was collected with a magnetic core, washed with deionized water until neutral, and vacuum dried to obtain Fe 3 O 4 Nanoparticles;
[0083] (3) Preparation of silanized Fe by sol-gel method 3 O 4 :Weigh Fe 3 O 4 (1.0 g) was completely dispersed in 250 mL of ethanol-water (4:1, V / V) solution, concentrated ammonia (4 mL) and TEOS (3 mL) were added, and stirred at room temperature for 8 h. After the reaction was completed, the reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and vacuum dried to obtain silanized Fe 3 O 4 Nanoparticles (Fe 3 O 4 @SiO 2 );
[0084] (4) Vinyl Fe 3 O 4 @SiO 2 Preparation: 3-methacryloxypropyltrimethoxysilane (8 mL) was dissolved in 160 mL of anhydrous ethanol, and then Fe 3 O 4 @SiO 2 (0.4g), N 2 The reaction product was collected with a magnetic core, rinsed with deionized water until neutral, and dried under vacuum at 50°C to obtain solid particles, namely Fe 3 O 4 @SiO 2 -CH=CH 2 ;
[0085] (5) Preparation of deep eutectic-based magnetic molecular imprinted polymer (DES-MMIP) by surface imprinting method: 0.35 mL of functional monomer (DES) and 50 mL of methanol were placed in a 250 mL three-necked flask and prepolymerized at 25 °C for 3 h. Then, Fe 3 O 4 @SiO 2 -CH=CH 2 (0.20 g), continue prepolymerization for 9 h, then add 4 mL of crosslinking agent ethylene glycol dimethacrylate (EGDMA) and initiator azobisisobutyronitrile (AIBN, 0.05 g), mix ultrasonically for 10 min, and then add N 2 Under protection, the reaction was stirred at 60 °C for 12 h. After the reaction, the reaction product was collected with a magnetic core, and the template was eluted with methanol:acetic acid (9:1, V / V) until doxycycline could not be detected in the eluent. The acetic acid was then removed by elution with ethanol and deionized water, and the mixture was vacuum dried at 50 °C to prepare DES-MNIP without adding the template molecule doxycycline (DOX).
[0086] The materials of Example 3 and Example 4 were characterized in terms of morphology:
[0087] (1) Scanning electron microscope
[0088] The morphology of DES-MNIP and DES-MNIP microspheres was characterized. Figure 1 As shown,
[0089] Fe 3 O 4 It has a regular spherical structure, relatively uniform particle size, and is covered by SiO 2 After encapsulation, the magnetic dipole attraction between the magnetic nanospheres was reduced, improving their dispersibility. However, the surface-modified 3-methacryloxypropyltrimethoxysilane caused aggregation between the nanospheres. DES-MMIP and DES-MNIP showed aggregation, where the interparticle gaps of DES-MMIP were sparser than those of DES-MNIP. This may be due to the presence of template molecules in DES-MMIP, which occupy specific spatial sites during the imprinting process, and the cavities left after elution by the eluent allow doxycycline to be specifically adsorbed.
[0090] (2) Infrared spectroscopy
[0091] The materials synthesized in each step of Example 3 were subjected to infrared characterization, and the characterization results are as follows: Figure 2 As shown, (a)Fe 3 O 4 ; (b) Fe 3 O 4 @SiO 2 ; (c) DES-MMIP; 586cm -1The characteristic peak at 3 O 4 Fe-O stretching vibration of nanoparticles; 947 cm -1 The absorption at 1097 cm is mainly from Si-O-Fe absorption. -1 The characteristic peak at 1639cm is the stretching vibration peak of Si-O-Si generated by the hydrolysis of ethyl orthosilicate. -1 There is a characteristic waveform of C=C at 1726cm -1 The absorption peak at 2957 cm is the C=O stretching vibration peak of 3-methacryloxypropyltrimethoxysilane. -1 There is an unsaturated CH stretching vibration peak at 1726cm -1 The absorption peak at is significantly enhanced. In addition, the peak intensity of the Fe-O characteristic peak is reduced due to the coating of the imprinting layer.
[0092] (3) X-ray diffraction pattern
[0093] Figure 3 for (a)Fe 3 O 4 ; (b) Fe 3 O 4 @SiO 2 (c) XRD spectrum of DES-MMIP, the diffraction peaks are almost the same, and the 2θ angle is similar to that of standard nano-Fe 3 O 4 The six characteristic diffraction peaks appear at 2θ=30.05°, 35.4°, 43.2°, 53.6°, 57.1°, and 62.8°, corresponding to Fe 3 O 4 The six crystal planes of Fe are (220), (311), (400), (422), (511) and (440). 3 O 4 @SiO 2 Stronger diffraction peaks can be seen at the same position as DES-MMIP, indicating that Fe 3 O 4 The diffraction peak position does not change after modification, indicating that the synthesized polymer material is highly crystalline and these magnetic particles are Fe 3 O 4 The core particle.
[0094] (4) Thermogravimetric analysis
[0095] Figure 4 for (a)Fe 3 O 4 ; (b) Fe 3 O4 @SiO 2 (c) Thermogravimetric analysis of DES-MMIP. From the thermogravimetric curve, we can see that the material has good thermal stability before 200°C, and the quality of the material does not change significantly with the increase of temperature. 3 O 4 , Fe 3 O 4 @SiO 2 and DES-MMIP lost 4.48%, 3.29% and 5.64% of their weights, respectively, suggesting that the loss was mainly due to the volatilization of residual organic solvent and water on the polymer. When further heated to 800 °C, Fe 3 O 4 and Fe 3 O 4 @SiO 2 The weight loss rates were 8.11% and 4.02%, respectively, while DES-MMIP underwent obvious thermal decomposition with a weight loss rate of 77.03%, which was attributed to the degradation of the imprinting layer, indicating that the imprinting was successful.
[0096] (5) Hysteresis loop
[0097] Figure 5 for (a)Fe 3 O 4 ; (b) Fe 3 O 4 @SiO 2 -CH=CH 2 (c) Magnetic hysteresis loop of DES-MMIP. It can be seen from the figure that the magnetization curve is centrally symmetrical, and the coercive force and residual magnetization intensity are almost zero, indicating that they both have superparamagnetism. Under the action of an external magnetic field, DES-MMIP can be quickly separated from the adsorption liquid. Fe 3 O 4 , Fe 3 O 4 @SiO 2 -CH=CH 2 The saturation magnetizations of DES-MMIP and DES-MMIP are 75.8emu / g, 63.3emu / g, and 32.2emu / g, respectively. This is because the non-magnetic surface modifier and polymer coated on the surface of the magnetic core cause the strength of the synthetic material to produce a shielding effect as the shell structure increases. However, the magnetization of DES-MMIP is still high enough to achieve rapid separation from the adsorption liquid under the guidance of an external magnetic field, and it can be used in actual sample separation and analysis.
[0098] (6) Adsorption performance study
[0099] Figure 6The results show that at room temperature, in a doxycycline solution (40 mL) with the same concentration (30 ug / mL), the adsorption capacity of DES-MMIP / DOX-NMIP (45 mg) changes with adsorption time (5-180 min). The adsorption amount of doxycycline increases rapidly within 60 min, and then the adsorption rate increases slowly until it gradually reaches equilibrium after 90 min. Figure 7 The adsorption of DES-MMIP / DES-MNIP (45 mg) in a series of doxycycline solutions with different concentrations (10-250 μg / L) is shown. As the doxycycline concentration increases, the adsorption amount of DES-MMIP (DOX-MNIP) also increases, and the adsorption amount of DOX by DES-MMIP is significantly higher than that of DES-MNIPs, which indicates that DES-MMIP has selective adsorption for doxycycline, strong recognition ability for doxycycline, and large adsorption capacity. Figure 8 The results show that the recovery rate of DES-MMIP for doxycycline adsorption is much higher than that of DES-MNIP in a mixed solution (40 mL) of doxycycline (30 μg / L) and its structural analogs (tetracycline (TC), oxytetracycline (OTC), chlortetracycline (CTC), and minocycline (MC)) of the adsorbent (45 mg). This may be due to the presence of many specific recognition sites for doxycycline in the imprinting layer. However, DES-MNIP has a low enrichment degree when adsorbing structural analogs, and the recovery rate is always lower than that of DES-MNIP, indicating that DES-MNIP has more surface imprinting sites.
[0100] From the above examples, it can be seen that the present invention provides a deep eutectic-based magnetic molecular imprinted polymer and its preparation method and application. The present invention adopts a coprecipitation method to prepare Fe 3 O 4 Nanoparticles were prepared by sol-gel method using tetraethyl orthosilicate to prepare Fe 3 O 4 The silanized Fe 3 O 4 Vinyl modification was performed to obtain Fe with uniform texture and good dispersion. 3 O 4 @SiO 2 -CH=CH 2, using this as an imprinted polymer magnetic core carrier, through surface imprinting technology, with doxycycline as a template, choline chloride-methacrylic acid (DES) as a functional monomer, ethylene glycol dimethacrylate as a crosslinking agent, azobisisobutyronitrile as an initiator, and methanol as a porogen to prepare a deep eutectic-based magnetic molecular imprinted polymer; the imprinted polymer prepared by the present invention can realize rapid separation of doxycycline under an external magnetic field, and has good adsorption efficiency and high selectivity. The preparation method of the present invention is simple, low in cost, and has good application prospects in complex sample matrices.
[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a deep eutectic-based magnetic molecularly imprinted polymer, characterized in that: The following steps are involved: (1) Dispersing Fe3O4 in an ethanol aqueous solution, then adding ammonia water and tetraethyl orthosilicate to react, collecting the reaction product and drying it to obtain Fe3O4@SiO2; (2) 3-methacryloxypropyltrimethoxysilane is mixed with anhydrous ethanol, and then Fe3O4@SiO2 is added to react, and the reaction product is collected and dried to obtain Fe3O4@SiO2-CH=CH2; (3) Doxycycline and DES functional monomers are prepolymerized in methanol, and then Fe3O4@SiO2-CH=CH2 is added for secondary prepolymerization, and then a crosslinking agent and an initiator are added for polymerization. The reaction product is collected and dried to obtain a deep eutectic-based magnetic molecular imprinting polymer.
2. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 1, characterized in that: The dosage ratio of Fe3O4, ammonia water and tetraethyl orthosilicate is 0.9-1.1 g: 3-5 mL: 2-3 mL; the mass volume ratio of Fe3O4 and ethanol aqueous solution is 0.9-1.1 g: 200-300 mL.
3. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 1 or 2, characterized in that: In the step (1), the reaction temperature is 20 to 40° C. and the reaction time is 7 to 9 hours; The ethanol aqueous solution is obtained by mixing ethanol and water in a volume ratio of 3 to 5:
1.
4. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 3, characterized in that: The usage ratio of the 3-methacryloxypropyltrimethoxysilane, anhydrous ethanol and Fe3O4@SiO2 is 6-10 mL: 150-170 mL: 0.3-0.5 g.
5. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 1, 2 or 4, characterized in that: In the step (2), the reaction is carried out under nitrogen protection, the reaction temperature is 60-70° C., and the reaction time is 11-13 hours.
6. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 5, characterized in that: The dosage ratio of the doxycycline, the DES functional monomer and methanol is 0.190-0.223 g: 0.3-0.37 mL: 40-60 mL; The mass ratio of doxycycline to Fe3O4@SiO2-CH=CH2 is 0.190-0.223:0.15-0.
25.
7. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 1 or 6, characterized in that: The prepolymerization reaction temperature is 20-30°C and the time is 1-4h; The secondary prepolymerization reaction time is 8 to 10 hours.
8. The method for preparing a deep eutectic-based magnetic molecularly imprinted polymer according to claim 7, characterized in that: The dosage ratio of the doxycycline, the crosslinking agent and the initiator is 0.190-0.223 g: 3-4 mL: 0.04-0.06 g; the polymerization reaction is carried out under nitrogen protection, the polymerization reaction temperature is 55-65° C., and the polymerization reaction time is 10-14 h; The cross-linking agent comprises ethylene glycol dimethacrylate, and the initiator comprises azobisisobutyronitrile.
9. The deep eutectic-based magnetic molecular imprinted polymer prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the deep eutectic-based magnetic molecular imprinted polymer according to claim 9 as a doxycycline adsorbent.